Ideologi dan Identitas Dalang dalam Seleksi Dalang Profesional Yogyakarta - Bambang Sulanjri (Jurnal Kajian Seni, 2017)
This study discusses a shadow puppet show packaged in a format in the Yogyakarta Professional Puppeteer Selection Year 2008. This research data is very unique because this kind of event does not happen again until 2016. Data were collected with audio visual recordings and direct observations. Data analysis uses formal analysis to review the performance structure, and content analysis based on various theories to reveal the ideology and identity that play a role in the show. The results of this study shows that the structure of the performance is not the same as that of the common shadow puppet show due to the adjustment of the puppeteers to the rules set by the organizers. Personal and collective identity appeared in the puppet show. Here, the puppeteers could express their personal ideas without eliminating their collective identity. There were three puppeteer ideologies: conservative, development and competitive ideologies, and the ccompetitive ideology is the dominant ideology.